The new pony - Amery, Heather; Cartwright, Stephen, 1947- (Tulsa, OK : EDC, 2004)
Poppy and Sam are surprised when their father buys them a pony from a neighbor who did not take care of it.
Originally published: London : Usborne, 1992.
Keywords: Farm life -- Juvenile fiction; Ponies -- Juvenile fiction; Farm life -- Fiction; Horses -- Fiction; Ponies -- Fiction